2013
DOI: 10.5581/1516-8484.20130099
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation treatment for high risk solid tumors in children with myeloablative chemotherapy and autologous hematopoietic progenitor stem cell transplantation

Abstract: BackgroundIn childhood cancer, consolidation treatment with chemotherapy followed by autologous hematopoietic progenitor stem cell transplantation is currently an accepted treatment modality in patients with high-risk solid tumors or in patients who have relapsed after conventional treatment. ObjectivesThe objective of this study was to describe the results of transplantation of a group of children who had high-risk solid tumors or relapsed after conventional chemotherapy regimens. MethodsA retrospective analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In conclusion, autologous HPC rescue is a safe procedure but we can only conclude that it provides benefits in patients with high-risk neuroblastoma and that further studies with a large group of patients and preferably in a randomized trial with an upfront approach in high-risk patients will be necessary to arrive at the conclusions that Vargas et al made in this report ( 1 ) .…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In conclusion, autologous HPC rescue is a safe procedure but we can only conclude that it provides benefits in patients with high-risk neuroblastoma and that further studies with a large group of patients and preferably in a randomized trial with an upfront approach in high-risk patients will be necessary to arrive at the conclusions that Vargas et al made in this report ( 1 ) .…”
mentioning
confidence: 64%
“…This paper reports on a small number of patients with a diverse group of diagnoses that were consolidated with high-dose therapy and rescued with autologous hematopoietic progenitor cells (HPC) ( 1 ) . One of the problems with this manuscript and many others is that the studies that have been performed and reported in the literature only reflect those patients who get the rescue and the survival advantage is from that point on.…”
mentioning
confidence: 99%